Intensity-modulated Radiotherapy for Rectal Cancer in the UK in 2020. Issue 4 (April 2021) - Hanna, C.R.; Slevin, F.; Appelt, A.; Beavon, M.; Adams, R.; Arthur, C.; Beasley, M.; Duffton, A.; Gilbert, A.; Gollins, S.; Harrison, M.; Hawkins, M.A.; et al.
Abstract: Aims: Preoperative (chemo)radiotherapy followed by total mesorectal excision is the current standard of care for patients with locally advanced rectal cancer. The use of intensity-modulated radiotherapy (IMRT) for rectal cancer is increasing in the UK. However, the extent of IMRT implementation and current practice was not previously known. A national survey was commissioned to investigate the landscape of IMRT use for rectal cancer and to inform the development of national rectal cancer IMRT guidance. Materials and methods: A web-based survey was developed by the National Rectal Cancer IMRT Guidance working group in collaboration with the Royal College of Radiologists and disseminated to all UK radiotherapy centres. The survey enquired about the implementation of IMRT with a focus on the following aspects of the workflow: dose fractionation schedules and use of a boost; pre-treatment preparation and simulation; target volume/organ at risk definition; treatment planning and treatment verification. A descriptive statistical analysis was carried out. Results: In total, 44 of 63 centres (70%) responded to the survey; 30/44 (68%) and 36/44 (82%) centres currently use IMRT to treat all patients and selected patients with rectal cancer, respectively. There was general agreement concerning several aspects of the IMRT workflow, including patient positioning, use of intravenous contrast and bladder protocols. Greater variation in practice was identified regarding rectal protocols; use of a boost to primary/nodal disease; target volume delineation; organ at risk delineation and dose constraints and treatment verification. Delineation of individual small bowel loops and daily volumetric treatment verification were considered potentially feasible by most centres. Conclusion: This survey identified that IMRT is already used to treat rectal cancer in many UK radiotherapy centres, but there is heterogeneity between centres in its implementation and practice. These results have been a valuable aid in framing the recommendations within the new National Rectal Cancer IMRT Guidance. Highlights: First national UK survey of rectal cancer IMRT use and practice. Considerable variation identified in IMRT implementation and practice. Results of survey informed recommendations within new national consensus guideline.